PENDIDIKAN KELUARGA DALAM PENGUATAN LITERASI DASAR PADA ANAK - Woro Wuryani; Via Nugraha (Jurnal Semantik, 2021)
This study is motivated by the low basic literacy problem of children. Based on news from Republika (Darma, 2020) states that the ability to process information through literacy or literacy culture in Indonesian society is very low. Chairman of the Indonesian Literacy Culture Development Forum Satria Darma said, based on research results from international institutions, the literacy culture of the Indonesian people is very low compared to other countries in the world. The reading position of Indonesian students ranks 57th out of the 65 countries studied (PISA). "PISA said, the literacy results of students in Indonesia are below level three and one, only 0.4% have literacy level four," he said. Based on these problems the researchers were moved to conduct a study about family education in strengthening basic literacy in children. in order to contribute to knowledge about how family education is to strengthen basic literacy in children. This study uses a qualitative descriptive approach, the problems in this study are described clearly based on the theory of family education in strengthening literacy in children so that they become provisions in educating children. from this research, it produces knowledge and ways to educate families to strengthen basic literacy in children.